Pengaruh Kompetensi, Indepedensi, dan Profesionalisme Auditor Internal dalam Mencegah Kecurangan (FRAUD) - Johan Erwin Panjaitan; Fitriana Fitriana; Didin Saepudin (Jurnal Syntax Transformation, 2021)
News about indications of fraud irregularities in a company committed by employees or employees makes us realize that we have to do something to fix the disorderly situation. This research aims to find out the influence of competence, independence and professionalism of internal auditors in preventing fraud. The theory used in this study is the Theory Agency. The population in this study was the internal auditor of PT ARI. This study used non probability sampling techniques with saturated samples. Samples were taken from all members of the population of 31 auditors. Data collection is done by questionnaire method. The data analysis technique used is multiple linear regression analysis. The results showed that the competence of internal auditors, the independence of internal auditors and the professionalism of internal auditors had a positive effect in preventing fraud at PT ARI Bandung